Exploring the Potential of Cobalt ferrites in the Supercapacitors Applications - Rana Rahul; Kaur Ranjeet; Raja Vaseem; Kumar Ajay (E3S Web of Conferences, 2024)
Supercapacitors have emerged as efficient energy storage devices for future autonomous gadgets due to their exorbitant power density, quick charging/discharging abilities, with prolonged cycle life. However, to meet demands such as high energy density and superior electrochemical performance, it is imperative to investigate different electrode materials. Primarily, electrode materials with a catholic potential range, low cost, and high specific capacitance are highly sought-after for supercapacitor applications. The cobalt ferrites (CoFe2O4) have emerged as materials with extraordinary specific capacitance, admirable redox response, are cost-effective, and are also environmentally friendly. In the present review article, we have discussed past reports where cobalt ferrites have been explored as potential candidates for supercapacitor applications.